The rift within an imagined community: understanding nationalism(s) in Bangladesh - Hossain, Ishtiaq; Khan, Mahmud Hasan (Brill, 2006)
The continuing debate in Bangladesh over the national identity of its people — whether one is a Bangali or Bangladeshi — is a post-1975 phenomenon. One of the main themes of the independence war (1971) was ‘Bangali nationalism’. However, it was replaced with ‘Bangladeshi nationalism’ by a military government following a bloody military coup in 1975. This major change in the label of the national identity of the people of Bangladesh requires explanation. A sharp distinction in the nature of politics in Bangladesh between the pre- and post-1975 era oﬀers an explanation of the politics of identity in Bangladesh. This study shows that the manifestations of these political identities have been represented discursively, according to the political ideologies adopted by the successive regimes in Bangladesh. This paper studies the material representations of national identity, speciﬁcally the discursive construction of national identity in Bangladesh. It investigates also whether national identity discourse is a creation of the political rhetoric during diﬀerent eras or it is “over-determined” in Althusserian terms. In other words, this paper questions the onto-logical basis of national identity in Bangladesh.